Celebrating the rich resources represented by African multilingualism and multiculturalism in education: discussant paper. Issue 2 (3rd April 2018) - Benson, Carol
ABSTRACT: This paper discusses the contributions to this special issue in the context of the African Renaissance and the subsequent need to re-define educational development from a multilingual, multicultural and pan-African perspective. Each contribution offers a different angle to the discussion: a critique of Arabization in Morocco, with questions about whether a new medium of instruction policy will prioritize people's own languages or French; an analysis of urban attitudes in Angola toward a new education policy providing for six mother tongues to be used in lower primary; a description of the challenges for stakeholders in the Seychelles to recognize that Seselwa, a creole, can be an acceptable medium of instruction; and an assessment of the opportunities and limitations in South Africa of classroom trans-languaging between African languages and English. A stronger voice needs to emerge on behalf of African languages and ways of knowing.